P157 Pattern of hepatitis a virus epidemiology in nursing students and adherence to preventive measures at two training wards of a university hospital. (1st September 2016) - Mereu, Noemi Maria; Pilia, Ilaria; Piazza, Maria Francesca; Spada, Laura; Lai, Alberto; Portoghese, Igor; Galletta, Maura; Coppola, Rosa Cristina; Campagna, Marcello
Abstract : Background: Nursing students can be exposed to patients with hepatitis A virus (HAV) and can represent a vehicle of transmission both for health personnel, patients and relatives. The aim of this study was to assess the risk of HAV infection in nursing students during their internship. Methods: A seroprevalence survey on HAV infection was performed on nursing students at the Cagliari university-hospital, together with the assessment of the compliance to preventive measures to decrease the risk of infection during their internship. Blood specimens were obtained from 253 students. All serum samples were tested for anti-HAV antibodies (IgG) by the enzyme-linked immunosorbent assay (ELISA). Compliance to preventive measures was recorded by trained personnel. Results: Overall HAV seropositivity in nursing students (mean age 24, range 17–45 years) was 3%. Compliance to preventive measures was not uniform (6%–76%) and extremely low in some specific measures targeted to decrease the oral-faecal transmission. Conclusions: The high proportion of susceptible nursing students can contribute to an increase in the risk of nosocomial transmission, especially when specific preventive measures are not completely applied. Nursing education packages, before starting medical internship, should be implemented in order to increase their compliance to preventive measures, especially in wards at higher risk. Vaccination should be considered in wards at higher risk. The study was conducted with the support of the Italian Ministry of Health, CCM Program 2013.